1963
DOI: 10.1254/jjp.13.82
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-Hydroxytryptamine on the Isolated Atrium of Rabbit

Abstract: There have been numerous observations to suggest that in mammals 5-hydroxy tryptamine acts as a humoral agents (1, 2). Though 5-HT is very widespread in the body, there has been no literature to show the amount of 5-HT in the heart of the mammals. But in the cyclostome heart it has been shown that the amount of 5-HT is (6). The latter authors confirmed that 5-HT, in concentration of 10-6, had a powerful stimulant action on the isolated auricle.Stimulation was, however, preceded by a slight and transient inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1965
1965
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…6). Indirect sympathomimetic actions of 5-hydroxytryptamine similar to those ob served in this study were reported in isolated rabbit hearts [4,11].…”
Section: Discussionsupporting
confidence: 85%
“…6). Indirect sympathomimetic actions of 5-hydroxytryptamine similar to those ob served in this study were reported in isolated rabbit hearts [4,11].…”
Section: Discussionsupporting
confidence: 85%
“…Toda (150) showed that 5-hydroxytryptamine (5-HT) has a positive chronotropic and inotropic effect on the isolated rabbit atrium after initial brief negative effects. He suggested that 5-hydroxytryptamine acts to liberate first acetylcholine (which accounts for the initial negative chrono and inotropic responses and can be accentuated by eserine), which in turn stimulates release of norepinephrine from myocardial nerve terminals or cells.…”
Section: Myocardial Wall Tension Was Measured With a Latex Balloon-comentioning
confidence: 99%
“…In reserpinized rabbits, however, serotonin does not produce a positive inotropic action (4). Accordingly, the serotonin induced increase in myocardial contractile force is presumably mediated by noradrenaline and adrenaline, which were liberated by the administration of serotonin .…”
mentioning
confidence: 92%
“…The positive inotropic action of serotonin (5-hydroxytryptamine) has extensively been demonstrated in the isolated perfused heart of cats, dogs and rabbits (1,2), in the isolated auricle of the rabbit's heart (3,4), in the cat papillary muscle (5), and in the heart of dog in situ (6). In reserpinized rabbits, however, serotonin does not produce a positive inotropic action (4).…”
mentioning
confidence: 99%